Intercellular adhesion molecule 1 serves as a primary cognate receptor for the Type IV pilus of nontypeable Haemophilus influenzae. (26th February 2016) - Novotny, Laura A.; Bakaletz, Lauren O.
Summary: Nontypeable Haemophilus influenzae (NTHI) utilizes the Type IV pilus (Tfp) to adhere to respiratory tract epithelial cells thus colonizing its human host; however, the host cell receptor to which this adhesive protein binds is unknown. From a panel of receptors engaged by Tfp expressed by other bacterial species, we showed that the majority subunit of NTHI Tfp, PilA, bound to intercellular adhesion molecule 1 (ICAM1) and that this interaction was both specific and of high affinity. Further, Tfp‐expressing NTHI inoculated on to polarized respiratory tract epithelial cells that expressed ICAM1 were significantly more adherent compared to Tfp‐deficient NTHI or NTHI inoculated on to epithelial cells to which ICAM1 gene expression was silenced. Moreover, pre‐incubation of epithelial cells with recombinant soluble PilA (rsPilA) blocked adherence of NTHI, an outcome that was abrogated by admixing rsPilA with ICAM1 prior to application on to the target cells. Epithelial cells infected with adenovirus or respiratory syncytial virus showed increased expression of ICAM1; this outcome supported augmented adherence of Tfp‐expressing NTHI. Collectively, these data revealed the cognate receptor for NTHI Tfp as ICAM1 and promote continued development of a Tfp‐targeted vaccine for NTHI‐induced diseases of the airway wherein upper respiratory tract viruses play a key predisposing role. Abstract : Nontypeable Haemophilus influenzae (NTHI) utilize Type IV pili (Tfp) for adherence to airway epithelial cells, shown herein to be mediated via engagement with ICAM1. Adherence of Tfp‐expressing NTHI was abrogated by pre‐incubation of airway cells with recombinant PilA protein or by silencing ICAM1 gene expression. Upper respiratory tract viral infection induced greater expression of ICAM1 by airway cells and further augmented NTHI adherence; thus promoting continued development of Tfp‐targeted vaccines for NTHI‐induced diseases wherein respiratory tract viruses play a role.